Na(+)/H(+) Exchange Activity in the Plasma Membrane of Arabidopsis - Qiu, Quan-Sheng (The American Society for Plant Biologists, 2003)
In plants, Na(+)/H(+) exchangers in the plasma membrane are critical for growth in high levels of salt, removing toxic Na(+) from the cytoplasm by transport out of the cell. The molecular identity of a plasma membrane Na(+)/H(+) exchanger in Arabidopsis (SOS1) has recently been determined. In this study, immunological analysis provided evidence that SOS1 localizes to the plasma membrane of leaves and roots. To characterize the transport activity of this protein, purified plasma membrane vesicles were isolated from leaves of Arabidopsis. Na(+)/H(+) exchange activity, monitored as the ability of Na to dissipate an established pH gradient, was absent in plants grown without salt. However, exchange activity was induced when plants were grown in 250 mm NaCl and increased with prolonged salt exposure up to 8 d. H(+)-coupled exchange was specific for Na, because chloride salts of other monovalent cations did not dissipate the pH gradient. Na(+)/H(+) exchange activity was dependent on Na (substrate) concentration, and kinetic analysis indicated that the affinity (apparent K(m)) of the transporter for Na(+) is 22.8 mm. Data from two experimental approaches supports electroneutral exchange (one Na(+) exchanged for one proton): (a) no change in membrane potential was measured during the exchange reaction, and (b) Na(+)/H(+) exchange was unaffected by the presence or absence of a membrane potential. Results from this research provide a framework for future studies into the regulation of the plant plasma membrane Na(+)/H(+) exchanger and its relative contribution to the maintenance of cellular Na(+) homeostasis during plant growth in salt.